Sistem Pendukung Keputusan Starting LineUp Tim Sepakbola Menggunakan Metode Perbandingan Eksponensial (MPE) - Andhika Pranadipa; Yufis Azhar; Agus Eko Minarno (Universitas Muhammadiyah Malang, 2022)
Football is one of the most popular sports in the world. Indonesian football, especially at the grassroots level, pays less attention to statistics in the line-up players selection, so in this study, a decision support system (DSS) will be implemented to assist football coaches at the grassroots level using the Exponential Comparison Method to select players based on match statistics. Statistical assessments will be assessed include, goals scored, missed kicks, kicks on target, assists, key passes, successful passes, successful dribbles, successful tackles, clearances, intercepts, saves, penalty saves and minutes played. It is expected that with this system, the selection of the starting line-up of players by the coach can be carried out objectively and can support the coach in making decisions.